2018
DOI: 10.1016/j.aller.2017.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Does atopy affect the course of viral pneumonia?

Abstract: When patients with mild-moderate pneumonia were compared to patients with severe pneumonia, frequency of atopy was not different between the two groups. However, parental asthma, ever wheezing and environmental tobacco smoke exposure are risk factors for severe viral pneumonia in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…On the other hand, it is also worth thinking whether allergic diseases could affect respiratory virus infections. A multicenter prospective study examined the effects of the presence of atopy, which was defined as positive skin prick tests to one or more allergens, on the course of disease in children hospitalized with viral pneumonia. In that study, atopy was found in 21.4% patients, while it showed there was no effect of atopic sensitization on the severity of viral pneumonia in children.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, it is also worth thinking whether allergic diseases could affect respiratory virus infections. A multicenter prospective study examined the effects of the presence of atopy, which was defined as positive skin prick tests to one or more allergens, on the course of disease in children hospitalized with viral pneumonia. In that study, atopy was found in 21.4% patients, while it showed there was no effect of atopic sensitization on the severity of viral pneumonia in children.…”
Section: Discussionmentioning
confidence: 99%
“…An association between childhood pneumonia and asthma has been noticed for long (2931). Parental asthma, earlier wheezing, and exposure to tobacco smoke are associated with more severe clinical course of pneumonia (32). In our study, asthma was slightly more common in RV-positive patients than others, but, contrary to our expectation, wheezing in auscultation of lungs was not more prevalent among RV-positive than RV-negative CAP patients.…”
Section: Discussionmentioning
confidence: 99%
“…20 On the other hand, atopic sensitization had no effect on the severity of viral pneumonia in children, as shown in a multi-center prospective study, but the history of allergic diseases such as atopic dermatitis, food allergy and drug allergy were associated with severe pneumonia. 21 In a previous study on 140 adult COVID-19 cases, allergic diseases and asthma showed much less prevalence compared to population levels, suggesting that allergy is not a predisposing factor for SARS-CoV-2 infection. 22 This study aims to investigate the clinical and laboratory characteristics of hospitalized COVID-19 pediatric patients, and to reveal the relationship between SARS-CoV-2 infection, immune response and allergic status, with a special focus on disease severity and allergy in patients.…”
Section: Introductionmentioning
confidence: 91%